EFFECTIVENESS OF ENGINEERING GROUP GUIDANCE SERVICES CINEMA THERAPY TO INCREASE SELF-CONFIDENCE FOR MADRASAH STUDENTS - Rambe, Afghan Bai Asy Ary; Harahap, Ade Chita Putri (Edukasi: Jurnal Pendidikan, 2024)
One of the functions of group guidance services is to train group members' self-confidence, supported by the use of cinema therapy techniques in using film media, it can have a positive effect on clients in increasing their understanding of something, including self-confidence. This research aims to determine the effectiveness of group guidance services using cinema therapy techniques in improving the self-confidence of Madrasah students. The research method used was quantitative with a pre-experiment design of a one-group pretest and a post-test design. The population in this study were all 7th-grade students at MTs. S P.P. Amiruddiniyah had as many as 132 people, with a sample of 10 students who had low self-confidence. Data was collected using a non-test instrument in the form of a self-confidence scale. Data analysis was carried out using the Wilcoxon Signed Ranks Test. The research results show that the significance value of asymp. Sig(2-tailed) ≤ 0.05, namely 0.005. Thus, it can be concluded that group guidance services using cinema therapy techniques are effective in increasing students' self-confidence.